INFORMATION PROCESSING WITH QUBITS IN A MICROWAVE FIELD - MOHAMED ABDELHAFEZ, HEBA KADRY (2015)
Recently, great interest has attracted many proposals to build and construct the quantum computer both theoretically and experimentally. The superconducting Josephson junc tions (Cooper-pair box) circuits is one of the most promising hardware architecture for the realization of a scalable quantum computer processor. The production, controlling and manipulation of the quantum bits are still not completely solved. In this thesis we studied the interaction of the multi-photon field with single Cooper-pair box. First, the theoretical model which describes our system is reported. The analytical expression of the reduced density operator of the cavity field and the Cooper-pair is calculated. The dynamical properties of various parameters on the mean number of the Cooper pairs are studied. It is shown that the system parameters play an important role in the dy namics of the qubits in the system.